Upaya Meningkatkan Jumlah Mahasiswa Baru Pada Universitas Panca Marga Probolinggo - Tumini Tumini (Fakultas Ekonomi Universitas Panca Marga, 2016)
Straiving increase the quantity of new students of the Panca Marga Univercity Probolinggo. From the general illustration five years later, the condition of the instituation to find out one problems is : the decrease of quantity students at 20013-2013 academic year. The decrease of the quantity students is threatment principally for the in instituition countinuity, so the thesis topic choice is what the efforting to increase the quantity of the students from 834 students at 2013-2014 to be up until 1500 student at 2014-2015. This thesis used the survey method to investigation and collected by : 1). Analysis document investigation, 2). Observation investigation, 3). Interview investigation, 4). Quisioner unvestigation. The data analysis by discription with percentation numerial for the data observation and used the SWOT analysis by the bussines management system. That means which the factor to be choose from the basic function is ready to use. So situational target can get. Internal and external analysis factor and indicator prepared to use for give point 8 point that decided. The solving problem alternative start from the function that have readyable low until the function that readyable high. From 12 basic function, decided 8 basic function and 7 basic function not yet readyable for as arrange : 1). Personal management function, 2). Equipment and material management function, 3). Production management function, 4). Transaction management function, 5). Market planning management function, 6). Customer target function, 7). Financial management function. The efforting to increase of the quantity the new students for arrange as : 1). Give program studies professional and good service, 2). For the faculty that has one program study to develop one, 3). The factor not have readyable yet change to be the factor readyable, 4). Make a hall, testroom/laboratorium for each faculty, 5). In order prepare the function as planning product research and growth developing product and marketing research. Keyword; increase, the quantity, new students, Univercity